Analisis Verba Dalam Novel Yorick Karya Kirana Kejora - Mika Sapitri; Rostina Taib; Muhammad Iqbal (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This study entitled Verb Analysis in Novel Yorick Karya by Kirana Kejora" The problem formulations are (1) what is the form of verbs in novel Yorick by Kirana Kejora, (2) what is the meaning of verbs in novel Yorick   by Kirana Kejora, and (3) how is the function of verbs in verbs in novel Yorick by Kirana Kejora,. The purpose of this research is to describe (1) the form of verbs in the novel Yorick by Kira Kejora, (2) the meaning of the verb in the novel Yorick by Kira Kejora, and (3) the function of the verb in the novel Yorick by Kira Kejora. This study uses a qualitative approach and descriptive methods. The data of this research comes from sentences containing verbs in novel Yorick by Kirana Kejora. The data collection technique was carried out using document review techniques. The data were analyzed through three stages, namely (1) identification, (2) classification, and (3) analysis. The results of this study can be stated as follows. First, based on the form of verbs, there are 85 data, namely 70 verb data in terms of morphology, 14 data on verbs in terms of syntax, and 3 verb data in terms of their relationship with nouns. Second, based on the meaning of verbs there are 11 data. All the data is divided into three meanings, namely the meaning of "action", the meaning of "process", and the meaning of "incident". Third, based on the level of function, there are 38 data divided into verbs that function as predicates totaling 9 data, 6 data subjects, 2 data objects, 9 complementary data, and 5 information explanations.